OPTIMALISASI PERAN IBU DALAM MENDUKUNG BUAH HATI DALAM MEMPEROLEH PENGALAMAN YANG MENYENANGKAN SELAMA PROSES TUMBUH KEMBANG DI POSYANDU RW 01 - Ai Fadillah (Jurnal JKFT, 2023)
ABSTRACTEarly Childhood (AUD) is a unique individual. Children have extraordinary abilities and talents which, when given the right stimulation, will make the child an extraordinary person as well. Early childhood is an individual figure who is undergoing a process of rapid growth and development which is fundamental for the next life. The process of growth and development at this time is at its peak. Children aged 0-6 years or commonly called the golden age, this period is a sensitive period for children to receive various efforts to develop their full potential. Good attention and support from parents and a conducive environment will optimize the growth and development of children. Development is a process of change that takes place in every stage of the child's age. Early childhood development is the progress experienced by children as a whole starting from physical, social and emotional abilities. The important role of parents in providing a pleasant experience for children with a strong bond between mother and child so that children are more confident, not afraid of new things, on the contrary this can foster children's trust in the world and both parents.